Intriguing Chinese culture - Miao Yaohua (Intriguing Chinese culture, 2017)
A generously illustrated series introducing traditional Chinese ideas and beliefs that are still relevant today. The series (Intriguing Chinese Culture) includes 4 books with subjects arranged in English alphabetic order. Wide range of topics covered, such as particular animals, legendary creatures, festivals, colours and numbers_ Interesting contrast between Western and Chinese beliefs, where applicable. Numerous illustrations and photos to bring Chinese culture alive. Relevant Chinese phrases and idioms with English translations for vocabulary expansion.